The mustard seed garden manual of painting =: chieh tzu yuan hua chuan, 1679-1701 : a facsimile of the 1887-1888 Shanghai edition with the text translated from the Chinese and edited by Mai-mai Sze - Wang, Kai, 1677-1705 author; Sze, Mai-mai, editor (Princeton, N.J. : Princeton University Press, 1956)
Includes index.